Yield in Coffee Cup (Coffea arabica L) according to the Roasting Process of Caturra and Bourbon Varieties - Díaz, Segundo (2023)
The objective of the research was to determine the cup yield of coffee, according to the roasting process of the caturra and bourbon varieties in three different times (8, 10 and 12 minutes), considering an initial sample entry temperature of 190°C and a final temperature for each time of (190ºC, 208ºC and 214ºC). The methodology used was a cross-sectional experimental type with a complementary randomized block design (DBCA), using the analysis of variance test (ANVA) and the Tukey comparison test at 5%. The results indicated that the bourbon variety is of better quality with a roasting time of 10 minutes and a cup yield of 84.23, while the caturra variety has the same roasting level, but a lower cup yield of 83.65, evaluated by two Q-Grader tasters from the INPROCAFE cooperative. In conclusion, the bourbon variety has a better cup yield (84.23) with a roasting time of 10 minutes compared to the other variety